Woodpecker wants a waffle - Breen, Steve (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
"Benny the woodpecker makes a brilliant plan to eat a tasty plate of waffles"--
Keywords: Determination (Personality trait) -- Fiction; Woodpeckers -- Fiction; Pancakes, waffles, etc. -- Fiction; Animals -- Fiction; Food habits -- Fiction